Broad Ligament Pregnancy: Facing the Battle Unarmed - Dandan Shi; Meenakshi Singh; Nihita Pandey; Ratna Biswas (Maternal-Fetal Medicine)
Abstract. Broad ligament pregnancy is defined as gestation that grows in the space formed by anterior and posterior peritoneal folds of the broad ligament. We report a case of 30 years old lady admitted to our hospital with the diagnosis of gravida 2, para 1, live birth 1, with 24 weeks of gestation with low lying placenta with anhydramnios. She was taken up for lower segment cesarian section at 28 weeks gestation in view of low lying placenta with chorioamnionitis. The broad ligament pregnancy was diagnosed peroperatively after identifying the anatomical relationship of the pregnancy. Sac was excised and margins secured after extraction of the baby and placenta. Patient had an uneventful postoperative period. Broad ligament pregnancy may be missed in antenatal period but in cases of displaced cervix, early onset unexplained anhydramnios, and failed induction of labor, it may raise high suspicion. Laparotomy/ laparoscopic management is the mainstay of management of broad ligament pregnancy.